INTERNET USE AMONGST SECONDARY SCHOOL STUDENTS IN KUALA LUMPUR, MALAYSIA - Wee, S.H. (Malaysian Journal of Library and Information Science, 1999)
This study identifies the pattern of Internet use among 608 upper secondary science students from fourteen schools in Kuala Lumpur, Malaysia. All schools have computers, out of which 9 have Internet facilities and 3 Internet terminals are located in the school resource centres. About 51.5% of respondent used the Internet. The main reasons for non-use are lack of skill and non-availability. The users mainly accessed the Net from their homes and acquired Internet skills by self-teaching or learning from friends. Slightly over 70% of Net users spent less than 5 hours a week on various functions, but few used it for study-related activities. The average time spent on the Internet was 4.89 hours per week. Most of the Net users (91.4%) explored the World Wide Web while 75.4% used E-mail, 52.1% used IRC or ICQ, 15.7% joined Newsgroups, 2.2% used it for downloading, and 0.6% used it for playing online games. Major problems faced were “lack of skills” and “lack of time”. The Internet was perceived to be a rich information reservoir that provides fast and efficient access to information. The majority believed that Internet did not affect their learning process, with 20.7% reporting a positive effect and 4.5% a negative effect. There were significant relationships between the use of Internet with gender, English grade, parents’ level of education, parents’ income, availability of Internet in school, and locality of Internet in school.